STRENUOUS MUSCULAR EXERTION IN THE POLAR CLIMATE AND ITS EFFECT UPON HUMAN WORK CAPACITY AND TOLERANCE TO COLD. - Andersen,K. Lange; Hellstrom,Bjorn; Eide,Rolf (1965)
The physiology of eight men who participated in a polar ice cap expedition was investigated with regard to work capacity and cold tolerance. Several test were administered to the subjects before and after the expedition such as tests of cold tolerance and exercise fitness. A delay in the retesting made it difficult to accurately evaluate the results, but in general the study confirms earlier observations on how a period of cold exposure and hard physical work affects aspects of physiology underlying tolerance to cold. (Author)